Anticipating elite capture: the social devaluation of municipal tap water users in the Phoenix metropolitan area. Issue 6 (18th August 2021) - Brewis, Alexandra; Meehan, Katie; Beresford, Melissa; Wutich, Amber
ABSTRACT: Characterizing subcultural models of tap water derived from interviews from 154 respondents in four neighbourhoods in the urban Southwestern United States, we identify sources of public discourses that support and anticipate passive elite capture. In accord with predictions, social devaluation of those who use tap water is situated with residents of a privileged exclusive community sector. This suggests the value of a broader conceptualization and an empirical model of elite capture in water resources: not just as a physical deviation of resources, but also as a discursive devaluation of public resources by specifically elite populations.